Seizure‐onset patterns in focal cortical dysplasia and neurodevelopmental tumors: Relationship with surgical prognosis and neuropathologic subtypes - Lagarde, Stanislas; Bonini, Francesca; McGonigal, Aileen; Chauvel, Patrick; Gavaret, Martine; Scavarda, Didier; Carron, Romain; Régis, Jean; Aubert, Sandrine; Villeneuve, Nathalie; Giusiano, Bernard; Figarella‐Branger, Dominique; et al. (Epilepsia (Copenhagen), 2016)
Summary Objectives The study of intracerebral electroencephalography (EEG) seizure‐onset patterns is crucial to accurately define the epileptogenic zone and guide successful surgical resection. It also raises important pathophysiologic issues concerning mechanisms of seizure generation. Until now, several seizure‐onset patterns have been described using distinct recording methods (subdural, depth electrode), mostly in temporal lobe epilepsies or with heterogeneous neocortical lesions. Methods We analyzed data from a cohort of 53 consecutive patients explored by stereoelectroencephalography (SEEG) and with pathologically confirmed malformation of cortical development (MCD; including focal cortical dysplasia [FCD] and neurodevelopmental tumors [NDTs]). Results We identified six seizure‐onset patterns using visual and time‐frequency analysis: low‐voltage fast activity (LVFA); preictal spiking followed by LVFA; burst of polyspikes followed by LVFA; slow wave/DC shift followed by LVFA; theta/alpha sharp waves; and rhythmic spikes/spike‐waves. We found a high prevalence of patterns that included LVFA (83%), indicating nevertheless that LVFA is not a constant characteristic of seizure onset. An association between seizure‐onset patterns and histologic types was found (p = 001). The more prevalent patterns were as follows: (1) in FCD type I LVFA (23.1%) and slow wave/baseline shift followed by LVFA (15.4%); (2) in FCD type II burst of polyspikes followed by LVFA (31%), LVFA (27.6%), and preictal spiking followed by LVFA (27.6%); (3) in NDT, LVFA (54.5%). We found that a seizure‐onset pattern that included LVFA was associated with favorable postsurgical outcome, but the completeness of the EZ resection was the sole independent predictive variable. Significance Six different seizure‐onset patterns can be described in FCD and NDT. Better postsurgical outcome is associated with patterns that incorporate LVFA.